2017
DOI: 10.1016/j.landurbplan.2017.01.014
|View full text |Cite
|
Sign up to set email alerts
|

Do acoustic indices reflect the characteristics of bird communities in the savannas of Central Brazil?

Abstract: Habitat loss and fragmentation represent two of the most significant threats to biodiversity. In some regions, like the Brazilian Cerrado, the deforestation rate can reach nearly 1 million hectares per year. Ecoacoustics and acoustic indices can be used to promote rapid assessments in threatened regions. We evaluated how two particular indices (the acoustic diversity index-ADI-and normalized difference soundscape index-NDSI) reflect bird species richness and composition in a protected area near Brasilia city. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
46
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 93 publications
(52 citation statements)
references
References 41 publications
5
46
0
1
Order By: Relevance
“…Similar analytical methods to those used here have been undertaken in previous studies on avian acoustics (e.g. Machado et al 2017). A semi-automated process can substantially reduce the time required for analysis, but introduces the potential for machine errors in call recognition, with both false negative and false positive classifications likely to result.…”
Section: Acoustic Data Analysismentioning
confidence: 89%
“…Similar analytical methods to those used here have been undertaken in previous studies on avian acoustics (e.g. Machado et al 2017). A semi-automated process can substantially reduce the time required for analysis, but introduces the potential for machine errors in call recognition, with both false negative and false positive classifications likely to result.…”
Section: Acoustic Data Analysismentioning
confidence: 89%
“…Differences in ADI and NDSI meanings correspond to differences in the species composition and structure of bird communities between the gallery and cerrado forest in Central Brazil. (Machado et al, 2017). The results of studies conducted at sites of varying degrees of degradation (from forests to agricultural land) in southeastern England and northwestern Ecuador showed that the greatest correlation (up to 65%) between acoustic indices and the number of bird species was observed in a temperate climate (Eldridge et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…; Machado et al. ). However, this method has two main drawbacks: (i) rotation procedures precludes simultaneous recording across sampling sites, potentially introducing bias from seasonal or weather changes, which must be accounted for; (ii) the number of monitoring days before rotating will influence species detectability, especially for rare species.…”
Section: Spatial Samplingmentioning
confidence: 98%